Predictors for Surgery in Shoulder Instability: A Retrospective Cohort Study Using the FEDS System. Issue 10 (7th October 2015) - Lebus, George F.; Raynor, Martin B.; Nwosu, Samuel K.; Wagstrom, Emily; Jani, Sunil S.; Carey, James L.; Hettrich, Carolyn M.; Cox, Charles L.; Kuhn, John E.; ,
Background: Shoulder instability is a common cause of pain and dysfunction in young, active patients. While studies have analyzed risk factors for recurrent instability and failure after instability surgery, few have examined which variables are associated with initial surgery in this patient population. Purpose: To identify variables that may be associated with surgical intervention in patients with shoulder instability in the context of the FEDS (frequency, etiology, direction, severity) classification, a system that may be useful in the surgical treatment of shoulder instability patients. Study Design: Cohort study (prognosis); Level of evidence, 2. Methods: A database of patients treated for shoulder instability from 3 separate institutions from 2005 to 2010 was generated using International Classification of Diseases–9th Revision data. Data were collected via retrospective review. Injury data were categorized according to the FEDS system. Data were analyzed for significance, with the primary outcome of surgical intervention. Summary statistics were used to assess which variables were associated with eventual surgery. To test the unadjusted bivariate associations between shoulder surgery and each data point, Pearson chi-square tests were used for categorical variables and Wilcoxon tests were used for continuous variables. Results: Over the study time period, 377 patients were treated for shoulder instability. Patients who had surgery were more likely younger, had recurrent instability, and had their initial injury while playing a sport. Most patients had anterior instability; however, there was a greater proportion of posterior instability patients in the operative group. Severity of dislocation, measured by whether the patient required help to relocate the shoulder, was not significantly associated with eventual surgery. While imaging was not available for all patients, surgical patients were more likely to have magnetic resonance imaging findings of anterior labral injury and less likely to have a supraspinatus or subscapularis tear. Conclusion: Patients who underwent surgery for shoulder instability were younger, more likely to have experienced recurrent instability, and more likely to have sustained their original injury while playing sports. The FEDS classification, particularly the frequency and etiology of the patient's shoulder instability, may be helpful in identifying patients with a higher likelihood of undergoing surgical treatment.